Transcriptomic Analysis on Responses of Murine Lungs to Pasteurella multocida Infection - Wu, Chenlu; Qin, Xiaobin; Li, Pan; Pan, Tingting; Ren, Wenkai; Li, Nengzhang; Peng, Yuanyi (Frontiers in Cellular and Infection Microbiology, 2017)
Pasteurella multocida infection in cattle causes serious epidemic diseases and leads to great economic losses in cultivation industry; however, little is known about the interaction between host and P. multocida in the lung. To explore a fully insight into the host responses in the lung during P. multocida infection, a mouse model of Pasteurella pneumonia was established by intraperitoneal injection of PmCQ2, and then transcriptomic analysis of infected lung was performed. P. multocida localized and grew in mouse lung, and induced inflammation in the lung, as well as mice death. With transcriptomic analysis, approximately 107 clean reads were acquired. 4236 differently expressed genes (DEGs) were detected during P. multocida infection, of which 1924 DEGs were up-regulated. By GO and KEGG enrichments, 5303 GO enrichments and 116 KEGG pathways were significantly enriched in the context of P. multocida infection. Interestingly, genes related to immune responses, such as pattern recognition receptors (PRR), chemokines and inflammatory cytokines, were significantly up-regulated, suggesting the key roles of these genes in P. multocida infection. Transcriptomic data showed that IFN-γ/IL-17-related genes were increased, which were validated by qRT-PCR, ELISA and immunoblotting. Our study is the first attempt to analyze the transcriptomic profile of P. multocida -infected lung, and our findings could provide valuable information with respect to better understanding the host response during P. multocida infection.